2021
DOI: 10.1002/cnr2.1525
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy is a risk factor of lymphopenia before adjuvant radiotherapy in breast cancer

Abstract: Background: Lymphopenia can decrease immune function of the host and is a known risk factor for poor prognosis in malignant tumors. Radiation induced lymphopenia was common in patients with breast cancer and was also reported to have a negative effect on long-term outcome.Aims: Lymphopenia may be associated with baseline immune status before radiotherapy (RT). This study aimed to explore the rate and risk factors of lymphopenia before start of the adjuvant RT in patients with breast cancer.Methods: Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(71 reference statements)
0
9
0
Order By: Relevance
“…This is consistent with the theory that when the preRT PLC is normal, the killing of circulation lymphocytes in blood by radiation plays the most important role in the reduction of PLC. However, 14.3% patients had preRT lymphopenia in this study, which was reported to be related with prior chemotherapy in our another study of 1012 patients with early or locally advanced breast cancer ( 28 ). Therefore, we also explored the relationship of EDIC and lymphopenia in this population.…”
Section: Discussionmentioning
confidence: 47%
“…This is consistent with the theory that when the preRT PLC is normal, the killing of circulation lymphocytes in blood by radiation plays the most important role in the reduction of PLC. However, 14.3% patients had preRT lymphopenia in this study, which was reported to be related with prior chemotherapy in our another study of 1012 patients with early or locally advanced breast cancer ( 28 ). Therefore, we also explored the relationship of EDIC and lymphopenia in this population.…”
Section: Discussionmentioning
confidence: 47%
“…Recently, a group at the University of Hong Kong published several studies that highlighted predictive factors of lymphocytopenia, including the use of VMAT, EDIC, and chemotherapy. 6,8,9 They also explored the potential determinants of radiation-induced lymphopenia using a machine learning approach. 10 The present study analyzed standard clinical and treatment-related factors to identify the predictive factors for lymphocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies on postoperative radiotherapy for patients with breast cancer, have identified various risk factors. Recently, a group at the University of Hong Kong published several studies that highlighted predictive factors of lymphocytopenia, including the use of VMAT, EDIC, and chemotherapy 6,8,9 . They also explored the potential determinants of radiation‐induced lymphopenia using a machine learning approach 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy Causing Immunodeficiency: Almost all chemotherapeutic agents such as cyclophosphamide, methotrexate, cisplatin, paclitaxel, and temozolomide cause damage to the bone marrow cells causing neutropenia and lymphopenia. 10 At around 1 -2 weeks after the completion of each cycle of chemotherapy neutrophil and lymphocyte counts drop to the lowest point 11 and this makes the cancer patients susceptible to infections including COVID-19. Limited data is available to study mortality risk estimates in cancer patients undergoing chemotherapy who become infected with COVID-19.…”
Section: IImentioning
confidence: 99%